Global research trends of non-performing loans: a bibliometric analysis / Nurul Farahana Mohd Nasir, Yan-Ling Tan and Roslina Mohamad Shafi - Mohd Nasir, Nurul Farahana; Tan, Yan-Ling; Mohamad Shafi, Roslina (UiTM Cawangan Johor, 2024)
Non-performing loans (NPLs) remain a significant challenge infinancial sectors worldwide. This study aims to explore the scholarly landscape of NPL research from a global perspective between 1970 and 2024 based on publication records retrievedf rom the Web of Science Core Collection (WoSCC). Using descriptive and bibliometric analyses, this study explores key publication trends, the most productive countries and authors, top-cited articles, and research clusters within NPLs research. The results suggest that the number of publications and citations has risen significantly over the years with the highest number of publications recorded in 2022. The USA dominates the ranking with the highest number of articles published, followed by China, England, Italy, and India. Moreover, the findings from the co-occurrence analysis reveal that previous studies mainly focused on the impacts of macroeconomic and bank-specific determinants on NPLs, with special attention given to the period of financial crisis, credit risk, commercial banks and Islamic banks. Similarly, bank effciency, stability, and performance are of great interest to researchers and data envelop analysis is employed to obtain efficiency estimates. Lastly, previous studies do not differentiate the NPLs at disaggregated levels. Future researchers can fill this gap by focusing on NPLs at sector or purpose levels. The impacts on NPLs are quantitatively diverse across sectors and purposes. Keywords: Bibliometric analysis, non-performing loans, NPLs, author keywords, keywords plus